Eksistensi Hibah yang Diperhitungkan sebagai Warisan Telaah Pasal 211: keterkaitan hibah dan warisan - Amir, Amirullah (STAI YAPIS Takalar, 2022)
This study aims to determine the relationship between grants and inheritance, to determine the position of the compilation of Islamic law in national law and to determine the analysis of grants that are calculated as inheritance. This study uses a sharia approach, namely a problem approach based on the Al-Quran and Hadith, as well as other agreed Islamic legal bases. The formal juridical approach is a problem approach based on the main law relating to legal principles, legal doctrine, regulations and the legal system related to the issue being discussed. And the sociological approach is to identify and conceptualize law with real and functional social institutions in real life systems. This means that the results of this research are expected to be able to answer the problems that exist in the community related to grants.